Oxford University Research Archive (ORA): Climate Research Collection - Partridge, J (2024)
Working with the departments within the University of Oxford, primarily with the Social Sciences Division, a 'Research Collection' focusing on the University of Oxford's research output regarding Environmental Sustainability and Climate Research, was created within ORA (Oxford University Research Archive) to showcase the research content.